BUILDING SECURITY SYSTEM USING GP2Y0A21YK0 INFRARED SENSOR AND ARDUINO UNO - Fahmy Rinanda Saputri; Nicholas Pranata; Vincentius Rayza Lee (Bakti Nusantara Institute, 2023)
The use of infrared radiation as a home security system is one of the technology improvisations that utilize physics phenomena. This research focuses on the designing of simple control systems based on Arduino Uno and GP2Y0A21YK0F infrared sensors along with other components. The working principle of this system starts when the IR sensor detects moving objects in the vicinity of the house in which infrared radiation is reflected and this gives outputs in the form of distance value from the display as well as movement and sound from servo to inform the occupants of the object’s whereabouts. Data obtained from the display system showed an approximation of the real distance value. Therefore, occupants can know the distance of the moving object.